Estudio de factibilidad para la creación de una empresa productora y comercializadora de puertas plegables denominada “Espacios SAS” en la ciudad de Pereira (2015)
This feasibility study is the creation of ESPACIOS SAS Company, which will be devoted to the development and commercialization of folding doors, they allow saving space thanks to its design that uses only the frame to open and close. To define whether the creation of the company is feasible it is from different methodological aspects that are important to give a focus to the project. Entering in the field is the study of market, to analyze demand applies survey to a defined sample in homes of levels 3 and 4 in the city of Pereira, then perform important questions on the acceptance of the product, this information is tabular and plotted for the quantitative analysis of information, this form determine some characteristics of the product that are important to customers and which must be adjusted in the project; for the analysis of the offer the different actors of the market, including competition, which has certain deficiencies that can be leveraged in favors of the company are evaluated. Subsequently is the technical study, which defines the size of the company is not so great, but if you must meet standards to comply with the requirements by the clients, similarly, the location of the plant in the sector of Cerritos in Pereira, is defined by taking into account various factors and machinery is identified Labor and raw material required for the operation of the company. This step environmental impact analyses also notably with the use of wood, as well as the strategies that must be implemented to counter it. The administrative and legal structure of the company is defined in the same way. To conclude whether the company is viable in all aspects, he is the financial study, this allows you to identify costs and expenses, as well as the most important of the project that are useful, among several additional indicators, which allow to make sound project decisions.